Inactivation of Human Factor VIII by Granulocyte Proteases - Váradi, Katalin; Marossy, Katalin; Asbóth, G; Elödi, P; Elödi, Susan (Thrombosis and Haemostasis, 1980)
The effect of human granulocyte proteases and related pancreatic enzymes on the procoagulant (VIII:C) and the von Willebrand (VIIIR:WF) activities of factor VIII was investigated. VIII:C appeared to be several hundred times more sensitive towards granulocyte enzymes than VIIIR: WF. The elastase-like protease (ELP) decreased both activities of factor VIII more effectively than the chymotrypsin-like enzyme (CLP). ELP increased co-operatively the inactivating effect of CLP. In the presence of a CLP-ELP mixture in a ratio of 3:1, the rate of inactivation of VIII:C was seven times as high as that with CLP alone.Factor VIII was more resistant towards the damaging effect of pancreatic enzymes. The rate of inactivation of VIII: C was about a thousand times and that of VIIIR:WF about a hundred times lower than those measured with the related granulocyte enzymes of the same proteolytic activity. The sensitivity of VIII: C towards proteolysis was not as pronounced with pancreatic enzymes as with granulocyte proteases.Our data suggest that, even though CLP and ELP are called "-like" enzymes, the specificity of granulocyte proteases is not identical with that of the pancreatic enzymes. The extreme sensitivity of VIII: C for granulocyte proteases may bring about blood coagulation disorders in certain pathological conditions.
Keywords: Factor VHI/procoagulant activity; Factor VIII/von Willebrand activity; Granulocyte proteases